Rice Farmers' Knowledge of Fertilizers Organic and Market Potential in Support Organic Farming Development (Case Study of Rice Farmers in the District Motilango (Gorontalo Regency) - Randi Mahmud; Supriyo Imran; Wawan K Tolinggi (Majapahit Journal of Islamic Finance and Management, 2026)
The development of organic farming is one of the efforts to realize a sustainable and environmentally friendly agricultural system. However, the success of its development is greatly influenced by the level of farmer knowledge and the potential of the organic fertilizer market. This study aims to analyze the knowledge of rice farmers regarding organic fertilizer and how the market potential supports the development of organic farming in Mootilango District. This study uses a qualitative descriptive approach with 12 informants, consisting of 10 rice farmers, 1 farmer shop owner, and 1 organic fertilizer producer. Data collection was carried out through in-depth interviews, field observations and documentation, then analyzed using SWOT analysis. The results of the analysis show that the IFAS value is 3.29 which indicates strong internal conditions, while the EFAS value is 3.58. The position of organic farming development is in Quadrant I, which indicates an aggressive strategy. Therefore, the recommended strategy is the SO strategy of optimizing farmer understanding through technological development, organic fertilizer promotion, increasing public awareness; (2) the WO strategy of strengthening the distribution of organic fertilizer, increasing farmer knowledge, increasing farmer skills;ST Strategy Price competitiveness, Organic selling value, Increasing the application of organic fertilizer; WT Strategy Anticipating negative perceptions about organic fertilizerThis strategy is expected to support increased use of organic fertilizers and encourage the development of organic farming in Mootilango District in a sustainable manner.